Peran Perempuan Dalam Pelestarian Lingkungan Menggunakan Sistem Agroforestri - Alvi Syahrin; Dahlia Kusuma Dewi; Nur Asiah; Peni Patriani; Andrio Bukit (Jurnal Ilmiah Penegakan Hukum, 2023)
Indonesia, especially Binjai City, uses an agroforestry system by utilizing the land of the residents of Binjai City by planting several cultivated plants, especially horticultural annuals and forest trees. The goal is to reduce the use of chemical pesticides and get the yield of land planted with horticultural crops in a relatively fast time, compared to forest crops whose productivity is relatively long. The sad thing is that the land will cause soil damage and will not become one of the providers of oxygen sources (O2) on Earth due to the reduced number of trees planted. There are also several other disadvantages, namely the competition between trees and horticultural crops in terms of fighting for nutrients and sunlight and the last weakness is the increasing labor costs, especially the role of women. The problem raised in this study is the role of women in environmental conservation using the Agroforestry system. The method carried out in this study is an observation method using a qualitative descriptive method that analyzes the problem under study. The result of her research is that the Government must conduct counseling or presentation of material about the Agroforestry system to women directly so that it is easier to understand